(E,Z)-1,1,1,4,4,4-Hexafluorobut-2-enes: hydrofluoroolefins halogenation/dehydrohalogenation cascade to reach new fluorinated allene - Kirij, Nataliia V.; Filatov, Andrey A.; Yagupolskii, Yurii L.; Peng, Sheng; Sprague, Lee (Beilstein Journal of Organic Chemistry, 2024)
A series of 2,3-dihalo-1,1,1,4,4,4-hexafluorobutanes and 2-halo-1,1,1,4,4,4-hexafluorobut-2-enes were prepared from commercially available hydrofluoroolefins 1,1,1,4,4,4-hexafluorobut-2-enes and their 1H, 19F and 13C chemical shifts measured. Some reactions of synthesized 2-halo-1,1,1,4,4,4-hexafluorobut-2-enes have been investigated. A simple, one-pot procedure for the preparation of a new allene (1,1,4,4,4-pentafluorobuta-1,2-diene) and some of its transformations is presented.
Keywords: allenes; dehydrohalogenation; halogenation; 1,1,1,4,4,4-hexafluorobut-2-enes; isomerization